Differences in health education using videos and flipsheets on participation interest post party KB for public mother in the hospital dr. Abdul Rivai Berau - Syahriati, Syahriati; Hadiningsih, Eka Frenty; Purwanti, Heni; Meihartati, Tuti (Institute Of Computer Science (IOCS), 2024)
Postpartum family planning is the initiation of the use of contraceptive methods within the first six weeks after delivery. Preliminary study at dr Abdul Rivai Hospital Berau, in July-September 2023, 29 postpartum mothers were using postpartum birth control 420 postpartum mothers, where there is no hospital program to attract interest in using postpartum birth control through health education using flipcharts or videos. This study aimed to find out the difference between health education using videos and flip sheets on interest in postpartum family planning participation. This was a quasi-experimental study with two groups of pre and post-test design. The population was postpartum mothers at Dr Abdul Rivai Hospital Berau in September 2023, numbered 120 people, with a sample of 40 people; the consecutive sampling technique included video media groups and flip sheets, 20 people each. Data analysis used the Wilcoxon test and Mann-Whitney test. This study showed the influence of health education using videos on interest in participating in postpartum family planning (p-value = 0.000). The use of flip sheets in health education influences interest in participating in postpartum family planning (p-value = 0.000). There was a difference in health education using videos and flip sheets on interest in participating in postpartum family planning (p-value = 0.022). This indicates that health education in video and flip sheets media has an influence and difference in increasing interest in postpartum family planning participation. Dr Abdul Rivai Berau Hospital expects to socialize postpartum family planning through video counseling regularly carried out, starting with the mother's pregnancy check